Pengaruh Penambahan Lumpur PDAM dan Zeolit sebagai Media Imobilisasi Bakteri terhadap Produksi Biogas dari Limbah Organik Pasar (Effect of Addition PDAM Sludge and Zeolite as Bacterial Immobilization Media on Biogas Production from Organic Waste) - Ivontianti, Wivina Diah; Rakasiwi, Rinjani Ratih; Asniawati, Dwi (Universitas Tanjungpura, 2020)
Abstract Organic waste can be processed into biogas through the anaerobic decomposition process. Anaerobic decomposition can be influenced by various factors including the addition of immobilization media. Cell immobilization is an attempt to increase the stability of the anaerobic process while reducing the potential for washout. Adding this solid material can increase reactor efficiency and can increase methane yield. The research on the addition of zeolite and PDAM sludge as immobilization media aims to find out how the effect of the addition of immobilized media, as well as the best composition between PDAM slurry and zeolite as immobilization media in the biogas production process from organic waste. The immobilization media used has three variations in the composition ratio between PDAM sludge and zeolites, namely 2:0, 2:1, 1:1 and a control reactor. Observation parameter are of VS, pH, concentration of methane gas and gas volume. Based on observations made, it was known that the addition of zeolite and sludge PDAM as a medium of immobilization in the biogas production process could increase biogas production and the concentration of methane produced. Of the three variations in the composition of the media used in this study, the composition ratio of 2: 1 gave the best biogas production results in the amount of 23.2844 L. As for the methane concentration, the overall reactor with the addition of immobilization media results in higher biogas concentrations and the reactor with the addition of media with a ratio of 2: 1 gave the largest methane concentration results. Keywords: biogas, immobilization, PDAM Sludge, zeolite Abstrak Sampah organik pasar dapat diolah menjadi biogas melalui proses penguraian anaerobik. Penguraian anaerobik ini dapat dipengaruhi oleh berbagai faktor diantaranya penambahan media imobilisasi. Imobilisasi sel adalah salah satu usaha untuk meningkatkan stabilitas proses anaerob sekaligus mengurangi potensi washout. Penambahan material padatan ini dapat meningkatkan efisiensi reaktor dan dapat meningkatkan yield metana. Penelitian bertujuan untuk mengetahui bagaimana pengaruh penambahan media imobilisasi tersebut, serta komposisi terbaik antara lumpur limbah PDAM dan zeolit sebagai media imobilisasi pada proses produksi biogas dari limbah pasar. Media imobilisasi yang digunakan memiliki tiga variasi perbandingan komposisi antara lumpur PDAM dan zeolit, yaitu 2:0, 2:1, 1:1 dan reaktor kontrol. Parameter pengamatan adalah nilai VS, pH, konsentrasi gas metana, dan volume gas. Berdasarkan hasil pengamatan yang dilakukan diketahui bahwa penambahan zeolit dan lumpur PDAM sebagai media imobilisasi pada proses produksi biogas dapat meningkatkan produksi biogas serta konsentrasi metana yang dihasilkan. Dari tiga variasi perbandingan komposisi media yang digunakan dalam penelitian ini, perbandingan komposisi 2:1 memberikan hasil produksi biogas terbaik yaitu sebesar 23,2844 L. Sedangkan untuk konsentrasi metana, reaktor dengan penambahan media imobilisasi menghasilkan konsentrasi biogas yang lebih tinggi dengan hasil terbaik yaitu variasi perbandingan 2:1. Kata kunci: biogas, immobilisasi, lumpur PDAM, zeolit